THE EFFECT OF USING SMART BOX MEDIA ON THE IPAS LEARNING OUTCOMES OF FOURTH-GRADE STUDENTS - Ulya Dorazatun; Muhammad Khozinul Huda; Susilawati (Jurnal Cakrawala Pendas, 2026)
This study was motivated by the low learning outcomes in the IPAS learning subject among fourth-grade elementary school students, which were attributed to the lack of innovative learning media and the prevalence of conventional teaching methods. The study aimed to determine the effect of using the Smart Box media on the learning outcomes of fourth-grade students in the IPAS learning subject regarding the topic “Me and My Needs”,as assessed from cognitive, affective, and psychomotor learning outcomess. This study employs a quantitative approach using a quasi-experimental design with an unequal control group. The sample consists of two groupes: an experimental group and control group and a control group, each comprising 21 students. Data collection techniques included tests, observations, and documentation. Data analysis was conducted using normality tests, homogeneity tests, N-Gain tests, and t-tests for independent samples with the assistance of SPSS. The results showed that the average posttest score for the experimental group was 81.90, higher than that of the control group, which was 67.14. The results of the t-test for independent samples showed a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant effect of the use of the Smart Box media on IPAS learning outcomes.